Electronic Payments: Building the Case for a National Initiative - Al-Khouri, Ali M. (Advances in Social Sciences Research Journal, 2014)
The explosion of the internet and mobile phones, as well as other rapid technological developments, has significantly influenced momentous changes in the payments market. Perceived as being more efficient and less expensive, electronic payments pave the way for the development of more sophisticated digital services in both the public and the private sector. This article provides an overview of electronic payment systems and their relation to recent developments in the United Arab Emirates (UAE). It summarizes existing card-based stored-value-payment initiatives in the UAE and presents the current identity management infrastructure in the country as a potential enabler to support the development of a more comprehensive national electronic payment system.